TOWARD CREATIVITY AND SPEAKING ABILITY OF EFL STUDENTS: A MIXED-METHOD STUDY - Abdullah, Debiga Fikky; Kristina, Diah; Sumardi, Sumardi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
The collaboration of indispensable creativity comprehension and the speaking ability is pivotally needed. The present study investigated the individual creativity and speaking ability of EFL learners correlation. There were 30 Indonesian students majoring in the English language who participated in this study. The questionnaires were employed in gaining the creativity values which are measured by Gough?s (1979) Creative Personality Scale (CPS), Zhou and George?s (2001) Creativity Scale, and the score from the sum of two previous scores when z-scored. The students? interview results were checked using the IELTS Speaking Test Descriptor. The finding of the study reveals that there is a statistically significant correlation between EFL learners? individual creativity and their speaking ability The latter is believed will redound to the benefit of society considering that speaking ability is essential demand, enabling it with the full understanding of creativity. This study will help the researcher to uncover critical areas in the educational process from which a new theory on learning English maybe arrive at.